KOLABORASI IMAN DAN LOGIKA: INTERPRETASI PEREMPUAN KANAAN DI DALAM MATIUS 15:22-28 - Samuel Lengkong (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
In Christianity, there are two conflicting extremes, one emphasizes logic, namely rationalists such as Rene Descartes and Immanuel Kant, and the other extreme emphasizes faith, which is a number of Pentecostal-charismatics. This paper aims to obtain a valid and highly anticipatory understanding, as well as to reveal in-depth meanings that are implicated for Christian faith and logic. Therefore, this research is very relevant and urgent to be researched. The method used in this research is a qualitative research method. The qualitative research method used by the researcher is library research. The results of this study with a number of interpretations carried out, the researchers found a sinergy of faith and logic that the Canaanite woman possessed and demonstrated in Matthew 15:21-28. The faith of the Canaanite woman stated by Jesus is the faith produced by the logic of the Canaanite woman's thinking. Faith and logic should go hand in hand, should not be separated between faith and logic. Faith and logic are like two eyes that must be opened to see life's problems.